The initial stage of ontogenesis Hosta ventricosa (Salisb.) Stearn. - I.V. Boyko (Інтродукція Рослин, 2009)
Investigation results of Hosta ventricosa (Salisb.) Stearn. ontogeny initial stages, in the conditions of National Dendrological Park Sofiyivka, during the first years of seedling vegetation are given.